Photographic Reproductions, Copyright and the Slavish Copy - Cogan, Terry S. (The Columbia Journal of Law & the Arts, 2013)
Despite years of training and experience, the professional museum photographer receives little respect from copyright law. His carefully crafted photographic reproductions of artwork are deemed unoriginal slavish copies, while he is styled a mere technician who fails to infuse those images with even a minimal degree of creativity. Vacationers’ amateur snapshots taken with point-and-shoot cameras are considered original works, while the images of the professional museum photographer are deemed undeserving of copyright protection. Commentators have applauded or condemned this conclusion based largely on policy considerations related to museums and the public domain. This is the first article to bring the tools of art and visual theory to bear on the question of whether the law’s refusal to extend copyright protection to photographic reproductions is conceptually sound. This Article argues that the law’s failure to protect such photographs is a profound mistake, having little to do either with the inherent creativity of such images or with any lack of talent in museum photographers. Rather, as a result of ingrained cultural habits, ordinary viewers (including judges, juries and legal commentators) tend to look through a photographic reproduction as though it were transparent and see only the artwork depicted in the photograph. In so doing, they attribute all creativity to the painter of the artwork-and ignore entirely the uniquely photographic attributes of the image they are actually looking at, as well as the creative input of the photographer responsible for that image.